Implementasi Pervasive Computing Pada Sistem Monitoring Konsumsi Daya Listrik Stop Kontak Rumah - Ikhwan Zulfy; Dahnial Syauqy; Sabriansyah Rizqika Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Power saving consumption is necessary. The power consumption of a house can be monitored through kWh meters. The usual kWh meter monitors the overall power consumption of the house, it doesn't measure the details of the total power consumption of the home. Therefore we need to monitor the system of electric power consumption in every room of the house. Based on that requirement, an electrical power consumption of the outlet system monitoring is available in every room of the house using pervasive computing method. The system is using some devices that is a smartphone application and 2 node devices comprising NodeMCU v1.0 as the microcontroller and the current YHDT SCT-013-020 sensor. The system requires some nodes and an application device to be connected in the same network through the websocket protocol. Device node and the application are communicating through a router. The node device processes the sensor readings and then sends the data to the application. The application will scan the IP subnet mask, if the IP adresses are detected and configured on port 19105, the IP will be identified as node device. Then the application will request the sensor data to the node device and display its data to the user. After the test results are done, it will be known that the system can perform discovery with an average total time of 11156.3 ms, then it will send and display the data via the websocket protocol and the smartphone application.